A Comparative Analysis of Speech Act Usage Between Retno Marsudi's and Sugiono's Speeches in Supporting Palestine at International Forums - Aprianti, Dinar Tjitra; Rusmana, Dadan; Budiarti, Dian (Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyses the use of speech act in the diplomatic speeches of Retno Marsudi and Sugiono in international forums supporting Palestine. Based on Searle’s speech act theory and Toulmin’s argumentation theory, this study explores how each diplomat used linguistics strategies to construct meaning and covey political support. The data collection techniques in this research are first, watching videos of Retno Marsudi’s and Sugiono's speeches at the 16th UN and BRICS Summit through YouTube. Second, transcribing the selected videos. Third, searching for their speech texts on the official website of the Ministry of Foreign Affairs of the Republic of Indonesia. Fourth, reading the text and then collecting data by selecting which phrases to take. The last is identifying the phrases that match the category characteristics. Using descriptive qualitative method in the analysis, Retno Marsudi tends to use directive speech acts to urge immediate action from the UN Security Council and commissive speech acts to emphasize Indonesia's commitment to justice. On the other hand, Sugiono uses expressive and directive speech acts to build international solidarity and invite Southern countries to support Palestine. The analysis shows that Retno Marsudi emphasizes direct conceptual meaning, while Sugiono uses associative meaning to strengthen global solidarity and justice. This difference reflects the rhetorical strategies used in accordance with their respective audiences and objectives in international forums. This research provides insight into the use of language in diplomatic forums that can influence policy in international relations.